Ways to Reduce the Proceeding Load, Alternative to Decriminalization - Kirill V. Muravyev (Сибирское юридическое обозрение, 2016)
This article analyzes the initiative of the Supreme Court of the Russian Federation concerning the decriminalization of certain crimes and increasing the amount of the theft of another's property for criminal responsibility. The author notes the expected positive effect and disadvantages of decriminalization, draws the attention to alternative ways to reduce load of pretrial investigation and court proceedings.